Changes in bone density measured by ultrasound of calcaneus in sedentary workers - Jasmina Bišćević-Tokić; Sanja Brekalo-Lazarević; Nedim Tokić; Sabina Bećirović; Selvedina Sarajlić Spahić (Medicinski glasnik, 2019)
Aim: To determine a degree of change in the bones of workers who spend their full time job in sitting position and to find a correlation between smoking and changes in bone structure. Methods: Examinees were 213 female workers who worked full time sedentary work in front of computer. Each worker was subjected to physical examination and ultrasonic osteodensitometry of calcaneus. Results: The average age of patients was 45.4 years. Changes in bone density were found in 110 (51.64%) workers. Correlation between smoker and non-smoker groups was positive, but "r" was higher in smokers than in non-smokers. It is worrying that 10 out of 22 persons in the group up to 30 years of age have osteopenia. Conclusion: Recommendation for regular annual control of bone density of the working group at risk regardless of age should be followed. Prescribing exercise for the working group at risk should be a significant part of preventive work in clinics of occupational medicine and sports.
Keywords: bone diseases; occupational health; osteopenia